Anti-epileptic effect of Ganoderma lucidum polysaccharides by inhibition of intracellular calcium accumulation and stimulation of expression of CaMKII α in epileptic hippocampal neurons. - Shu-Qiu Wang (Public Library of Science (PLoS), 2014)
Purpose To investigate the mechanism of the anti-epileptic effect of Ganoderma lucidum polysaccharides (GLP), the changes of intracellular calcium and CaMK II α expression in a model of epileptic neurons were investigated. Method Primary hippocampal neurons were divided into: 1) Control group, neurons were cultured with Neurobasal medium, for 3 hours; 2) Model group I: neurons were incubated with Mg(2+) free medium for 3 hours; 3) Model group II: neurons were incubated with Mg(2+) free medium for 3 hours then cultured with the normal medium for a further 3 hours; 4) GLP group I: neurons were incubated with Mg(2+) free medium containing GLP (0.375 mg/ml) for 3 hours; 5) GLP group II: neurons were incubated with Mg(2+) free medium for 3 hours then cultured with a normal culture medium containing GLP for a further 3 hours. The CaMK II α protein expression was assessed by Western-blot. Ca(2+) turnover in neurons was assessed using Fluo-3/AM which was added into the replacement medium and Ca(2+) turnover was observed under a laser scanning confocal microscope. Results The CaMK II α expression in the model groups was less than in the control groups, however, in the GLP groups, it was higher than that observed in the model group. Ca(2+) fluorescence intensity in GLP group I was significantly lower than that in model group I after 30 seconds, while in GLP group II, it was reduced significantly compared to model group II after 5 minutes. Conclusion GLP may inhibit calcium overload and promote CaMK II α expression to protect epileptic neurons.